2015
DOI: 10.1016/j.ijdevneu.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular adaptations to chronic hypoxia in the growth restricted lamb

Abstract: Chronic moderate hypoxia induces angiogenic adaptation in the brain, reflecting a modulatory role for oxygen in determining cerebrovascular development. Chronic intrauterine fetal hypoxia, such as occurs in intrauterine growth restriction (IUGR) is likely to lead to a reduction in oxygen delivery to the brain and long-term neurological abnormalities. Thus we investigated whether vascular remodeling and vascular abnormalities were evident in the brain of IUGR newborn lambs that were chronically hypoxic in utero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(104 citation statements)
references
References 69 publications
11
93
0
Order By: Relevance
“…Although remodelling may help preserve energy under detrimental intrauterine circumstances, the postnatal implications of these adaptations have not been well investigated. In fact, a recent study demonstrated compromised structural integrity and stability of the cerebral microvasculature in IUGR lambs, increasing the blood-brain barrier permeability and their risk for cerebral haemorrhages [41]. …”
Section: Potential Consequences Of Prolonged Brain-sparingmentioning
confidence: 99%
See 3 more Smart Citations
“…Although remodelling may help preserve energy under detrimental intrauterine circumstances, the postnatal implications of these adaptations have not been well investigated. In fact, a recent study demonstrated compromised structural integrity and stability of the cerebral microvasculature in IUGR lambs, increasing the blood-brain barrier permeability and their risk for cerebral haemorrhages [41]. …”
Section: Potential Consequences Of Prolonged Brain-sparingmentioning
confidence: 99%
“…Based on these studies it has even been proposed that increased CBF reflects advancing stages of brain injury; not a protective mechanism against it [54,55,57]. As described previously, IUGR may be associated with vascular remodelling and reduced vasoreactivity [18,39,40,41,42]. The increased CBF may in part be a direct consequence of disturbed circulatory regulation.…”
Section: What Is Protected By Brain-sparing?mentioning
confidence: 99%
See 2 more Smart Citations
“…New insights suggest that chronic intrauterine hypoxia results in cerebrovascular remodelling [17], which may limit the cerebral autoregulatory response to hypoperfusion [6]. In fact, our SGA-hsPDA neonates demonstrated similar MABP, pulse pressure and SpO 2 to AGA-hsPDA neonates.…”
Section: Discussionmentioning
confidence: 72%